PENGARUH FLUKTUASI HARGA EMAS DAN TINGKAT INFLASI TERHADAP PENYALURAN PEMBIAYAAN GADAI EMAS PADA BJB SYARIAH - Eva Kholifah; Isfandayani Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This research was conducted to determine the effect of gold price fluctuations and levels on the distribution of rahn financing on gold pawn products at Bank BJB Syariah KCP Cikarang for the 2017-2020 period. Hypothesis testing using multiple linear regression analysis. The study's results partially show that the fluctuation variable in the price of gold has a positive and significant effect on the distribution of rahn financing. At the same time, the inflation rate variable has no significant effect on the distribution of rahn financing. Simultaneously, the independent variables of gold price fluctuations and the inflation rate significantly affect the dependent variable of rahn financing distribution, with an R Square value of 0.705 or 70.5%. At the same time, other factors influence the remaining 29.5%. These factors include income, location of operational offices, number of customers, and service products provided. Sharia is better than Bank BJB Syariah.